CT-like images of the sacroiliac joint generated from MRI using susceptibility-weighted imaging (SWI) in patients with axial spondyloarthritis. Issue 2 (28th May 2021) - Deppe, Dominik; Hermann, Kay-Geert; Proft, Fabian; Poddubnyy, Denis; Radny, Felix; Protopopov, Mikhail; Makowski, Marcus R; Diekhoff, Torsten
Abstract : Background: To analyse the added value of susceptibility-weighted imaging (SWI) compared with standard T1-weighted (T1) MRI for detecting structural lesions of the sacroiliac joint (SIJ) in patients with axial spondyloarthritis (axSpA) using CT as reference standard. Material and methods: Sixty-eight patients with suspected or proven axSpA underwent both MRI and CT of the SIJ on the same day. Two readers separately scored CT, T1 and SWI for the presence of erosions, sclerosis and joint space changes using an established 24-region SIJ model. Disagreement was resolved by a third reader. Diagnostic accuracy (McNemar test), Cohen's kappa (k), sensitivity (SE) and specificity were calculated on the joint level using CT as reference. Results: In CT, 38 joints showed erosions, 67 sclerosis and 37 joint space changes. Agreement with CT for erosions was 92.6% (k=0.811 (0.7–0.92)) in SWI and 87.5% (k=0.682 (0.54–0.82)) in T1 (p=0.143) and agreement for sclerosis 84.6% (k=0.69 (0.57–0.81)) and 62.5% (k=0.241 (0.13–0.35)) (p<0.001), respectively. This resulted in superior SE of SWI (81.6% vs 73.7%) for erosions and sclerosis (74.6% vs 23.9%) at a minor expense of SP. No differences were detected for joint space changes. Conclusion: In patients with axSpA, SWI depicts erosions and sclerosis more accurately than T1 spin echo MRI at 1.5 T.